Perilaku Pelanggan E-commerce Bahan Makanan Siap Masak dan Katering Sehat dalam Pemenuhan Kebutuhan Makanan Sehat pada Kondisi Pascapandemi Covid-19 - Elfa, Muhammad Okiba Jauhari; Utami, Hesty Nurul; Saidah, Zumi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The COVID-19 pandemic and the new normal conditions have resulted in changes in the way customers choose to shop for groceries, either physically at stores or online. Additionally, the new normal encourages people to pay more attention to a healthy lifestyle and consume nutritious food to maintain their immune systems. In response to these changes, food retail businesses, especially those offering ready-to-cook ingredients and healthy catering services, need to strive to retain customers by providing an online platform for ordering food, making customers feel more comfortable. This research aims to analyze the behavior of customers who use e-commerce for ready-to-cook ingredients and healthy catering in the post-pandemic condition. The study employs a quantitative research design with a descriptive approach. Data was collected from 300 customers of e-commerce for ready-to-cook ingredients and healthy catering. The research findings indicate that the primary reason for customers to make online purchases of ready-to-cook ingredients and healthy catering is the convenience of finding products that meet their needs and preferences. The majority of customers made their first purchase during the new normal conditions, and the subscription duration was predominantly over 9 months. Other research results show that the average purchase frequency is 2.18 times per week, with an average transaction value reaching Rp263,165.00.